Polycystic Ovarian Syndrome in Female players - Zahra, Syeda Maryam; Ahmed, Bilal (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
P Polycystic Ovarian Syndrome (PCOS) is quiet common gynecological disorders in recent times and has affected adversely the population. It causes infertility among females by disturbing the ovulatory process during menstruation. It impairs the female endocrine system and causes an increased level of male hormones. It has multiple etiologies such as genetic, environmental, life style but the pathogenesis is not clear. Molecular pathways and key players involved are yet ambiguous. It is polygenic with multiple etiologies and multiple symptoms. PCOS arise during puberty and a marked feature is insulin resistance. Awareness regarding PCOS among females is very less and they are unaware mostly about this condition. More researches are required for awareness regarding management of PCOS through life style modification such as diet, physical activity. Diagnosis and treatment should also be done timely at an early phase.